1992
DOI: 10.1056/nejm199211193272106
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of Physicians' Ownership of Health Care Facilities — Joint Ventures in Radiation Therapy

Abstract: Joint ventures in radiation therapy appear to have adverse effects on patients' access to care. They also appear to increase the use of services and costs substantially. Some indicators show that joint ventures cause either no improvement in quality or a decline. Our results add to the evidence indicating that physicians' self-referral generally has negative consequences. We recommend legislation to ban ownership of joint ventures by referring physicians. Such legislation needs to be carefully designed in orde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0
1

Year Published

1995
1995
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(66 citation statements)
references
References 16 publications
1
64
0
1
Order By: Relevance
“…Equipment owners tended to order more procedures, although there were no identifiable medical reasons for doing so. The investigators concluded that equity ownership of medical equipment, and the potential to profit from its use, can lead to overutilization (Hillman et al 1990;Mitchell and Sunshine 1992).…”
Section: Ownership Return On Equity and Incentives To Lower Qualitymentioning
confidence: 99%
“…Equipment owners tended to order more procedures, although there were no identifiable medical reasons for doing so. The investigators concluded that equity ownership of medical equipment, and the potential to profit from its use, can lead to overutilization (Hillman et al 1990;Mitchell and Sunshine 1992).…”
Section: Ownership Return On Equity and Incentives To Lower Qualitymentioning
confidence: 99%
“…14 US data suggest that physician ownership of IHFs increases the number of referrals and leads to higher costs. 15 Physicians who owned and operated diagnostic imaging equipment in their offices were up to 7 times more likely to obtain radiologic examinations than were physicians who always referred patients to radiologists. 16,17 In addition, the charges per episode of care were significantly higher for self-referring physicians.…”
Section: Defining Kickbacks and Self-referralmentioning
confidence: 99%
“…Internal referral can be lucrative. Mitchell and Sunshine (1992) and Swedlow et al (1992) offer considerable evidence that physicians use joint venture affiliations to "skim the cream" from the pool of patients by self-referring those patients with the most generous insurance, and then ordering costly procedures at a rate that exceeds the national average. In fact, internal referral is deemed to be sufficiently lucrative that joint venture affiliations are thought to place physicians in ethical jeopardy.…”
Section: The Economics Of Group Practicementioning
confidence: 99%